Efficacy of opioids for traumatic pain in the emergency department: a systematic review and Bayesian network meta-analysis - Fu, Yawen; Liu, Qiang; Nie, Hu (Frontiers in Pharmacology, 2023)
Aim: To systematically assess and rank the efficacy of opioid medications for traumatic pain in the emergency department in terms of pain relief, adverse events and rescue analgesia. Methods: Four databases were systematically searched until 26 September, 2022: PubMed, Embase, Cochrane Library, and Web of Science. Outcomes were pain relief, adverse events (dizziness, hypotension, pruritus, sedation), and rescue analgesia. For each outcome, network plots were drawn to exhibit direct and indirect comparisons, and rank probabilities were utilized to rank the efficacy of different opioids. Results: Twenty studies of 3,040 patients were eligible for this network meta-analysis. According to the rank probabilities, the top three analgesic medications for pain relief may be sufentanil (78.29% probability of ranking first), buprenorphine (48.54% probability of ranking second) and fentanyl (53.25% probability of ranking third); buprenorphine (31.20%), fentanyl (20.14%) and sufentanil (21.55%) were least likely to cause dizziness; the top three analgesic medications which were least likely to cause hypotension were buprenorphine (81.64%), morphine (45.02%) and sufentanil (17.27%); butorphanol (40.56%), morphine (41.11%) and fentanyl (14.63%) were least likely to cause pruritus; the top three medications which were least likely to cause sedation were hydrocodone+acetaminophen (97.92%), morphine (61.85%) and butorphanol (55.24%); patients who received oxycodone (83.64%), butorphanol (38.31%) and fentanyl (25.91%) were least likely to need rescue analgesia in sequence. Conclusion: Sufentanil, buprenorphine and fentanyl may be superior to other opioid medications in terms of pain relief and the incidence of dizziness, hypotension and pruritus, which might be selected as opioid analgesics for traumatic pain in the emergency setting.